2008
DOI: 10.1002/adma.200702554
|View full text |Cite
|
Sign up to set email alerts
|

Control of Electric Field Strength and Orientation at the Donor–Acceptor Interface in Organic Solar Cells

Abstract: Electrical doping is essential to achieve efficient photocurrent extraction in small‐molecular‐weight organic solar cells. It is shown that such doping creates strong electric fields at the donor‐acceptor interface that prevent geminate electron–hole recombination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
97
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(99 citation statements)
references
References 27 publications
2
97
0
Order By: Relevance
“…Additionally, polymer:fullerene solar cells are not intentionally doped like their inorganic counterparts or like many small molecule solar cells 11 and therefore rely on selective contacts and the difference in work function between electrodes for efficient charge collection. However, several studies have found evidence for unintentional doping [12][13][14][15][16][17][18][19] and discussed the consequences for device behaviour 6,[20][21][22][23][24][25][26][27][28][29][30] . Whilst the origin of this doping is unclear 15 , its effects on photovoltaic performance can be substantial; however many recent analyses of device performance neglect doping 8,[31][32][33] despite the fact that the influence of doping and the electric field on charge carrier collection is well known for a long time 34 and wellstudied for instance in the field of quantum dot photovoltaics 35,36 .…”
mentioning
confidence: 99%
“…Additionally, polymer:fullerene solar cells are not intentionally doped like their inorganic counterparts or like many small molecule solar cells 11 and therefore rely on selective contacts and the difference in work function between electrodes for efficient charge collection. However, several studies have found evidence for unintentional doping [12][13][14][15][16][17][18][19] and discussed the consequences for device behaviour 6,[20][21][22][23][24][25][26][27][28][29][30] . Whilst the origin of this doping is unclear 15 , its effects on photovoltaic performance can be substantial; however many recent analyses of device performance neglect doping 8,[31][32][33] despite the fact that the influence of doping and the electric field on charge carrier collection is well known for a long time 34 and wellstudied for instance in the field of quantum dot photovoltaics 35,36 .…”
mentioning
confidence: 99%
“…Design rules targeting enhanced exciton and charge diffusion or exciton splitting are, however, hard to come by, since the underlying microscopic mechanisms are not well understood. Efficient exciton dissociation, for example, has been attributed to the assistance of charge separation by a gradient in the free-energy landscape [132,133], structural heterogeneity as a function of distance to the interface [134], doping and charged defects [135], increase in entropy as the electron and hole move away from the interface [136], formation of hot CT states [137], or long-range tunneling [138]. Tuning optical absorption profiles, by contrast, is a more manageable approach to enhance the external quantum efficiency of single-junction devices.…”
Section: The Acceptor-donor-acceptor Puzzlementioning
confidence: 99%
“…To explain this mystery, various researchers have been actively discussing the exciton dissociation process and have proposed several explanatory mechanisms such as the contribution of entropy (dimensional effect), the hot charge-transfer (CT) state, doping or defects, and structural heterogeneity. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Among these, a strong candidate is the hot CT mechanism. 1, [22][23][24][25][26][27][28] In our previous study, we proposed a theoretical method to consider the hot CT state and examined the exciton dissociation process at the donor-acceptor interface.…”
Section: Introductionmentioning
confidence: 99%